Reviews Include In The Categories Of Providing Information Or Utterances Hate - Susila Susila; Danang Wahyu Muhammad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Reviewing part of consumer rights as described in Article 4 of the Consumer Protection Act, complaints and opinions in the review are part of Electronic word-of-mouth (e-WOM). This activity is very beneficial for business actors in the field of information and advertising. This study uses normative research sourced from previous research and binding regulations. This study discusses the provisions of the review included in information or hate speech and how business ethics are the limitations of the review. The submitted review will be included in the information stipulated in the binding legal provisions. The freedom of opinion in the proposed study has limitations, namely mutually beneficial business ethics as desired